Teaching, reflecting, and learning: The value of an intercalated medical education programme. (3rd May 2020) - Muir, Fiona; Bruce, Jack; McConville, Kevin
Abstract: Objectives: Teaching programmes within medicine focus primarily on pathways of a shorter length with little regard to teaching lasting longer than a month. This study is different from other studies as it examines the benefits of a nine month-long medical education degree programme and its impact beyond graduation. This study set out to explore the impact of a medical education intercalated degree programme for its graduates and their careers. Methods: A small scale, exploratory qualitative case study was conducted with 10 graduates of an intercalated degree programme. Results: The findings highlight the longer term value of an intercalated degree programme with particular emphasis on academic and personal skills; research and teaching skills; independence and confidence; its impact on future practice and the notion that 'student as teacher' programmes are a valuable asset to medical education as a whole. Participants advocated more teaching opportunities as a core longitudinal teaching component in preparation for the teaching responsibilities in their working lives. Conclusions: The programme enables the development of a range of academic and personal skills, with particular emphasis on research and teaching skills, independence and confidence.